Investigating ESP Teachers' Perceptions Towards The Possibility Of Implementing Team Teaching In Business English Courses: The Case Of ESP Teachers At The Faculty Of Economic Sciences, Commerce And Management Sciences At Ghardaia University (مجلة الواحات للبحوث والدراسات, 2020)
This research is conducted to portray the perceptions and views ESP teachers hold towards team teaching and the possibility of implementing this method in their business English courses at the faculty of Economic Sciences, Commerce and Management at the University of Ghardaia. This exploratory study investigates how ESP teachers perceive team teaching as a method of teaching and the extent to which they are apt to cooperate and adopt this approach in future. A group discussion and a questionnaire are used to gather data which are analyzed quantitatively, qualitatively and interpretatively. The results show that the majority of the teachers are apt to adopt this method in their business courses emphasizing that the managerial staff should implement it and provide a special training to avoid any misunderstanding.Key words- team teaching, teachers' perceptions, ESP courses, business English